Peaches and crocs: A story of gratitude for nurses - Resha, Cheryl Ann (American Nurse Today: Insights, 2018)
My story began when I was 49 years young and told I had Stage IV colorectal cancer. That was almost 12 years ago, and today I am one of the fortunate ones—not only has it been almost 12 more years of living, but my oncologist has used the word “cured”. Like most cancer patients and …
Keywords: dept.nur; ⛔ No DOI found